PENGARUH GAYA KEPEMIMPINAN INITIATING STRUCTURE TERHADAP ORGANIZATIONAL COMMITMENT MELALUI ROLE STRESS DI PT.COCA-COLA BOTTLING INDONESIA JAWA TIMUR DI RUNGKUT SURABAYA - YOBEE, MAGDALENA (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The purpose of this study was to examine the leadership style of initiating structure to Organizational Commitment with Role Stress in PT. Coca-Cola Bottling Indonesia Jawa Timur di Rungkut Surabaya.The study involved 150 respondents. The sampling technique used purposive sampling method. using SEM analysis (Structural Equation Modeling). Results showed that initiating structure leadership style influence on Organizational Commitment, Role Stress effect on Organizational Commitment, initiating structure leadership style influence on Role Stress and Role Stress as an mediator variable in initiating structure leadership style influence on Organizational Commitment.